2016
DOI: 10.1016/j.jembe.2016.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Auditory evoked potential audiograms in post-settlement stage individuals of coral reef fishes

Abstract: Just after the reef colonization, fish species could use the acoustic cue to settle on different suitable habitats. In the present study, we used the auditory evoked potential (AEP) technique to measure and compare the detection abilities in five coral reef fish species, with some of these species that are found in the same habitat. We also examined the effect of fish size on sensitivity at the species level. All studied species except one showed size-related changes in sensitivity characterized by either a de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
2
5
0
Order By: Relevance
“…8) showed decreasing amplification with increasing otolith-bladder distance. These results support previous studies that observed ontogenetic decreases in auditory sensitivity and speculated that ontogenetically increasing distances between the bladder and inner ear was a potential cause (Egner and Mann, 2005;Colleye et al, 2016). At larger fish sizes, the ontogenetically increasing bladder volume appeared to partially compensate for the amplification loss produced by greater otolithbladder distance.…”
Section: Ontogenetic Changes In Predicted Pressure Sensitivitysupporting
confidence: 91%
“…8) showed decreasing amplification with increasing otolith-bladder distance. These results support previous studies that observed ontogenetic decreases in auditory sensitivity and speculated that ontogenetically increasing distances between the bladder and inner ear was a potential cause (Egner and Mann, 2005;Colleye et al, 2016). At larger fish sizes, the ontogenetically increasing bladder volume appeared to partially compensate for the amplification loss produced by greater otolithbladder distance.…”
Section: Ontogenetic Changes In Predicted Pressure Sensitivitysupporting
confidence: 91%
“…In post-larval reef fish, audiograms based on sound pressure showed that the best hearing sensitivity is between 200 and 600 Hz [15,61,64,[67][68][69]. The frequencies that allowed them to hear the reef from the greatest distance during daytime were in the same frequency range.…”
Section: Comparisons With Audiograms: Fishmentioning
confidence: 99%
“…The frequencies that allowed them to hear the reef from the greatest distance during daytime were in the same frequency range. Based on the audiograms (SPL) of post-larval reef fish [15,61,64,65,[67][68][69] S2 and S3). These distances were smaller during the night except for species such as M. kuntee, which are able to hear higher frequencies (Figures 7A and 8).…”
Section: Comparisons With Audiograms: Fishmentioning
confidence: 99%
“…< 200 Hz). Moreover, low frequencies produced by ships overlap directly with the hearing ranges of recently settled damselfishes (30-1000 Hz) [2,43,44]. Previous studies have found that different noise sources can have differential effects on fishes.…”
Section: Plos Onementioning
confidence: 99%